MENINGKATKAN PEMAHAMAN KONSEP PECAHAN MELALUI KONTEKS KISAH SAHABAT RASULULLAH SEBAGAI MODEL NILAI ISLAM DAN MULTIKULTURAL DI SDN NO 100215 PERSIAPAN MOSA JULU - Harahap, Rita Nur`ain; Fata, Nahriyah (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This study aims to improve fourth-grade students' understanding of fraction concepts at SDN No 100215 Persiapan Mosa Julu through the context of the Prophet's companions' stories as a model of Islamic and multicultural values. The problems identified were students' low understanding of fraction concepts and lack of integration of Islamic character values in mathematics learning. This study used Classroom Action Research (CAR) method with two cycles. Each cycle consisted of planning, implementation, observation, and reflection stages. The research subjects were 24 fourth-grade students from various ethnic backgrounds in the Mandailing area. Research instruments included fraction concept understanding tests, student activity observation sheets, and student response questionnaires. The results showed significant improvement in fraction concept understanding from cycle I to cycle II. The average test score increased from 65.8 in cycle I to 83.3 in cycle II. Learning completeness increased from 62.5% to 87.5%. Student activities also showed improvement from sufficient to good category. The integration of Islamic and multicultural values through the Prophet's companions' stories proved effective in increasing student motivation and understanding.